Caregivers' attitudes toward potential robot coworkers in elder care - TURGUT, TÜLAY (SPRINGER LONDON LTD, 2019)
Technological advances in robotics increase progressively. Elder care is one of the work areas which have potential to involve robotic workforce. So, it is important to focus on interaction between humans and potential robot workers to prepare the organization for possible challenges. The current study examined the relationships between trust in robots and anthropomorphism of robots, intention to work with robots and preference of automation levels. For this purpose, 102 caregivers who work for elder care in a nursing home (aged between 19 and 40) participated in an experimental study. According to the results, anthropomorphism of robots did not make any difference in terms of trust in them. Trust in robots was significantly related to intention to work and preference of automation levels. Organizations may consider employees' trust in robots as an important factor before adapting them to workplace area.
Keywords: Elder care; Robots; Automation; Trust in robots; Anthropomorphism; Intention to work; PERSPECTIVE-TAKING; SOCIAL ROBOTS; TRUST; AUTOMATION; MACHINE; ANTHROPOMORPHISM; INTENTION; MODEL; INCREASES; BEHAVIOR